Simulation of the morphological structures of electrospun membranes. Issue 1 (11th August 2017) - Feng, Yan; Sun, Runjun; Chen, Meiyu; Liu, Chengkun; Wang, Qiushi
ABSTRACT: In this study, we proposed a model for the morphological structure of electrospun membranes; it was different from the random distribution of fibers in a nonwoven. On the basis of our observation and analysis of the jet path by a high‐speed camera and the electrospun membranes by scanning electron microscopy, we proposed the base circle/deposition circle model of electrospun membranes. The base circle was used to position the deposition circles. The deposition circles, distributed on or around the base circle at a specific proportion, represented the distribution of the electrospun fibers on the collector. The pore characteristics and fiber distribution were compared between the electrospun membrane and simulated membranes with different spinning times; this verified that they had similar distribution trends. A membrane was simulated with a similar magnification ratio to the actual membrane. This further verified the model. This model could be used for the homogeneity simulation of an electrospun membrane in multinozzle electrospinning, and this may be helpful for predicting electrospun membranes in practical applications. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45653. Abstract :